Argon Plasma Coagulation for Proctitis: A Meta-Analysis - Fisca Syofi Arrasyi; Saptino Miro (HM Publisher, 2025)
Background: Proctitis, encompassing various etiologies, significantly diminishes patient quality of life. Argon plasma coagulation (APC) has emerged as a potential therapeutic modality, yet its efficacy and safety profile remain to be fully elucidated. This meta-analysis aimed to rigorously evaluate the effectiveness and safety of APC across diverse proctitis subtypes. Methods: A comprehensive search of PubMed, Embase, and the Cochrane Library databases was conducted, spanning 2013 to 2023, to identify pertinent studies. Randomized controlled trials (RCTs) and observational studies comparing APC with alternative treatments or placebo in proctitis management were included. The primary outcome was clinical improvement, defined as symptom reduction or amelioration of endoscopic findings. Secondary outcomes encompassed adverse events and quality of life metrics. Results: A total of 15 studies (5 RCTs and 10 observational studies) encompassing 2042 patients met the inclusion criteria. APC demonstrated a significant association with clinical response improvement compared to other treatments or placebo (OR 2.58, 95% CI 2.14-3.12, p<0.001). Subgroup analysis revealed APC's efficacy in both radiation-induced and non-radiation-induced proctitis. Adverse event incidence was comparable between APC and other treatments, with no significant differences in severe complications. Conclusion: APC appears to be an effective and safe therapeutic option for various proctitis subtypes, warranting consideration in clinical practice.